Progesterone levels and days to luteolysis in mares treated with intrauterine fractionated coconut oil - Diel de Amorim, Mariana; Nielsen, Kayla; Cruz, Raissa Karolliny Salgueiro [UNESP]; Card, Claire (Elsevier, 2016)
Intrauterine plant oil infusion, including fractionated coconut oil, has been previously found to be a safe, inexpensive, and reversible method of prolonging the luteal phase in mares when administered on Day 10 of the estrous cycle. Our objective was to understand the uteroovarian response to the administration of fractionated coconut oil infusion in the uterus of diestrous mares. We hypothesized that intrauterine coconut oil administration on Day 10 would prolong luteal life span in a dose-dependent fashion and would result in higher serum progesterone levels than untreated mares at the expected time of luteolysis. Light-horse mares (n = 18) were examined using transrectal palpation and ultrasonography to determine if they had a normal interovulatory interval and were then examined daily in estrus until the day of ovulation (Day 0) and then every other day during an estrous cycle. Jugular blood was drawn on Day 11, Day 13, Day 15, and Day 17, centrifuged, and serum stored until assayed for progesterone (P4; Siemens Coat-a-Count Progesterone RIA, Los Angeles, CA, USA). Mares were randomly assigned to treatment and studied over one to two estrous cycles with a rest cycle after each treatment cycle. Groups were: control (n = 5), fractionated coconut oil 1.0 mL (Miglyol 810; Sasol Oil, Witten, Germany) infused in the uterus with an artificial insemination pipette on Day 10 (Group 1; n = 5) and fractionated coconut oil 0.5 mL infused in the uterus with an embryo transfer gun, on Day 10 (Group 2; n = 5). All statistical analyses were performed using analytical software (Stata SE, version 13.1, College Station, TX, USA) at P < 0.05. Data were first evaluated using the Shapiro–Wilk test for normality. Differences between groups in days to luteolysis (DTL) were examined using analysis of variance and Bonferroni, and the effect of day and treatment on P4 levels were examined using the Kruskal–Wallis and Dunn's all pairwise test. There was a significant difference in DTL between the groups (P = 0.0083), with fewer DTL in Group 1 compared to control (P = 0.011) and to Group 2 (P = 0.034). There was a significant effect of day (P < 0.0001) on P4 levels with Day 11 P4 levels higher than Day 15 and Day 17 and Day 13 P4 levels higher than Day 15 or Day 17 (P < 0.03). There was a significant effect of treatment group (P = 0.0098) on P4 levels with control and Group 2 levels higher than Group 1 mares (P = 0.0012, P = 0.0495, respectively). We concluded that intrauterine administration of 1 mL of fractionated coconut oil lowered P4 levels in diestrus in a dose-dependent fashion and did not prolonged the luteal phase of the mares.
Keywords: Coconut oil; Days to luteolysis; Mare; Progesterone